2020
DOI: 10.3390/jcm9061695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Single Mosaic Embryo Transfer: High-Level or Low-Level Mosaic Embryo, Does It Matter?

Abstract: Recently, reports showed that embryos identified as mosaic after preimplantation genetic testing for aneuploid (PGT-A) could result in live birth with lower pregnancy and higher pregnancy loss rates compared with euploid embryos. However, the effects of mosaicism level on reproductive outcomes remain controversial. This study aimed to examine the level of mosaicism on pregnancy outcomes. Single mosaic embryo transfer was offered to 108 women who only had mosaic embryos. Mosaic embryos were labeled by utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 34 publications
(57 reference statements)
1
34
0
Order By: Relevance
“…In addition, 147 embryos were from patients who had an abnormal karyotype were used for analysis of positive controls. 36 2018 May 24 NGS Whole blastocyst NGS Tsuiko 37 2018 June 14 NGS ICM NGS Popovic 38 2018 July 58 NGS TE/ICM NGS Chuang 39 2018 December 29 NGS TE/ICM NGS Victor 16 2019 January 100 NGS TE/ICM NGS Victor 40 2019 February 8 NGS TE/ICM NGS Popovic 41 2019 April 45 NGS Blastocyst outgrowth NGS Lawrenz 42 2019 June 84 NGS TE/ICM NGS Huang 43 2019 July 50 NGS Whole blastocyst NGS Treff 44 2019 August 14 NGS TE SNP array Munne 45 2020 January 57 NGS TE NGS Ou 46 2020 January 63 NGS Whole blastocyst NGS Sachdev 47 2020 February 32 NGS TE/ICM NGS Girardi 9 2020 March 88 NGS TE/ICM NGS Navratil 48 2020 April 75 NGS TE/Whole blastocyst NGS Rubio 49 2020 May 64 NGS ICM NGS Lin 50 2020 June 41 NGS ICM NGS Abbreviations: aCGH, array comparative hybridization; CGH, comparative genomic hybridization; ICM, inner cell mass; NGS, next-generation sequencing; qPCR, quantitative real-time PCR; PGT-A, preimplantation genetic testing for aneuploidy; SNP, single nucleotide polymorphism; TE, trophectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 147 embryos were from patients who had an abnormal karyotype were used for analysis of positive controls. 36 2018 May 24 NGS Whole blastocyst NGS Tsuiko 37 2018 June 14 NGS ICM NGS Popovic 38 2018 July 58 NGS TE/ICM NGS Chuang 39 2018 December 29 NGS TE/ICM NGS Victor 16 2019 January 100 NGS TE/ICM NGS Victor 40 2019 February 8 NGS TE/ICM NGS Popovic 41 2019 April 45 NGS Blastocyst outgrowth NGS Lawrenz 42 2019 June 84 NGS TE/ICM NGS Huang 43 2019 July 50 NGS Whole blastocyst NGS Treff 44 2019 August 14 NGS TE SNP array Munne 45 2020 January 57 NGS TE NGS Ou 46 2020 January 63 NGS Whole blastocyst NGS Sachdev 47 2020 February 32 NGS TE/ICM NGS Girardi 9 2020 March 88 NGS TE/ICM NGS Navratil 48 2020 April 75 NGS TE/Whole blastocyst NGS Rubio 49 2020 May 64 NGS ICM NGS Lin 50 2020 June 41 NGS ICM NGS Abbreviations: aCGH, array comparative hybridization; CGH, comparative genomic hybridization; ICM, inner cell mass; NGS, next-generation sequencing; qPCR, quantitative real-time PCR; PGT-A, preimplantation genetic testing for aneuploidy; SNP, single nucleotide polymorphism; TE, trophectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas only 1/10 samples with full or mosaic partial chromosome abnormalities were confirmed and the rest were euploid. These data may explain the reduced clinical pregnancy and live birth rates and increased miscarriage rates reported following transfer 14‐16 . Also, triploid embryos, which are sometimes misclassified as normally fertilised two‐pronucleate zygotes, 38,39 can only be identified by copy number analysis alone in male embryos by mosaic loss of the X and Y chromosomes and not in 69 XXX females.…”
Section: Discussionmentioning
confidence: 99%
“…However, both methods have also highlighted that, in addition to full aneuploidies, chromosomal mosaicism, indicated by intermediate copy number changes, and partial (or segmental) chromosome copy number abnormalities are relatively common even among trophectoderm cells biopsied at the blastocyst stage. Following an initial report of healthy live births resulting from transfer of embryos with only mosaic changes detected by array CGH, 13 there is now increasing clinical evidence that many of these embryos are viable and should be considered for transfer 14‐16 . However, pregnancy rates are lower and genetic counselling is recommended 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost none of the mosaic aberrations in transferred embryos from our group exceeded 50% borderline. Lin et al [14] demonstrated that mosaics, higher than 50%, still result in live birth cases, however, miscarriage levels are 25% higher, when compared to low-level mosaics. The reported case of Kahraman et al [15], where healthy offspring with 2% cells with monosomy of autosome 2 was born, does not exclude the possibility, that there could be more similar cases after the transfer of mosaic embryos.…”
Section: Discussionmentioning
confidence: 99%